2017
DOI: 10.1093/mnras/stx1921
|View full text |Cite
|
Sign up to set email alerts
|

The Maria asteroid family

Abstract: The Maria asteroid family is a group of S-type asteroids. Its location adjacent to the left side of the 3J:-1A mean-motion resonances could be the reason for the absence of the left side of the 'V' shape in the (a, 1/D) domain. This family can be considered as a likely source of ordinary chondrite-like material. In this work, we make use of the time dependence of the asymmetric coefficient A S describing the degree of asymmetry of the C distribution of a fictitious Maria family generated with the value of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…23, with C Y E = 6.5 × 10 −5 au calculated from Eq. 20 where C = 1.1 × 10 −4 au in agreement with the results of (Aljbaae et al 2017a) for the age of the Maria family. The value of µ α = 0.87 and C EV = 4.6 × 10 −5 au calculated using Eq.…”
Section: A34 Mariasupporting
confidence: 86%
“…23, with C Y E = 6.5 × 10 −5 au calculated from Eq. 20 where C = 1.1 × 10 −4 au in agreement with the results of (Aljbaae et al 2017a) for the age of the Maria family. The value of µ α = 0.87 and C EV = 4.6 × 10 −5 au calculated using Eq.…”
Section: A34 Mariasupporting
confidence: 86%
“…As reported above, the odds of asteroids from the J3:1 reaching an Eros-like orbit are ~20%, less likely than the inner main belt but not unreasonably low. Several published dynamical ages for the Maria family have suggested that it is ~2 Ga (e.g., Spoto et al, 2015;Aljbaae et al, 2017) or possibly 3 ± 1 Ga (Brož et al, 2013). The collision probability of main belt asteroids with (170) Maria is Pi = 2.923 × 10 -18 km -2 yr -1 , about 1.1 times the value used for the above age calculation.…”
Section: Interpretation Of Eros's Crater Recordmentioning
confidence: 77%
“…Currently, there should be about ten family members larger than 1 km in diameter, and many more smaller objects, orbiting in near-Earth space. finally, Aljbaae et al (2017) found that the Maria family could contribute some objects to the NEOs population, though the contribution of bodies larger than 3 km in size should be practically zero at present.…”
Section: Families Delivering Fragments On Earthmentioning
confidence: 93%